2022
DOI: 10.1177/15347354221124861
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic Potential of Natural Triterpenoid Cucurbitacin B Against Cholangiocarcinoma Cells by Targeting Src Protein

Abstract: Owing to the crucial role of Src in cancer metastasis, interruption of Src and its signaling has been considered a promising strategy for cancer metastasis treatment. Cucurbitacin B, a dietary triterpenoid, has been shown to possess anti-proliferative and apoptosis-inducing activities in cholangiocarcinoma (CCA) cells via suppressing the activation of FAK which is a main downstream Src effector. We hypothesized that cucurbitacin B might act as a Src suppressant which conferring anti-metastasis effect against C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…shown that CuB has anti-migration ability in cancer cell lines (Huifu et al, 2023;Kaewmeesri et al, 2022). Although anti-migration activity seems to be due to inhibition of STAT3 and enhancement of STAT1 signaling, our results suggest that the reason could be binding G-actin (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…shown that CuB has anti-migration ability in cancer cell lines (Huifu et al, 2023;Kaewmeesri et al, 2022). Although anti-migration activity seems to be due to inhibition of STAT3 and enhancement of STAT1 signaling, our results suggest that the reason could be binding G-actin (Guo et al, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…Besides, the F‐actin polymerization rate was analyzed and compared with the other actin‐binding drugs, jasplakinolide and cytochalasin D, and it has been realized that CuI (200 nM) reduced the polymerization rate of F‐actin nearly as much as jasplakinolide and cytochalasin D. In our study, the formation of large cytoplasmic actin aggregates was observed in HUVECs by fluorescence microscopy, similar to Kenecht's study (Knecht et al., 2010 ). Recent studies have shown that CuB has anti‐migration ability in cancer cell lines (Huifu et al., 2023 ; Kaewmeesri et al., 2022 ). Although anti‐migration activity seems to be due to inhibition of STAT3 and enhancement of STAT1 signaling, our results suggest that the reason could be binding G‐actin (Guo et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can be used at many stages of the drug design process to: (i) anticipate the binding mode of already known ligands; (ii) find novel and potent ligands; and (iii) as a tool to forecast binding affinity [46,47]. In our study, we used molecular docking of compounds 3-6 employing freely available PyRx (AutoDock) software [48,49].…”
Section: Methods Used For Molecular Dockingmentioning
confidence: 99%
“…Open Babel and Autodock‐vina wizard and Python in‐built in PyRx software, whereas Open Babel is used for energy minimization of active ligand molecules and Vina wizard is used to perform docking of selected prepared molecules. Molecular docking analysis was visualized by Pymol and 2D and 3D interaction was examined using Pymol software (Kaewmeesri et al, 2022).…”
Section: In‐silico Characterization Of Formononetin As a Cox Nrf‐2 An...mentioning
confidence: 99%